Spatiotemporal Variations of Vegetation Net Primary Productivity and Its Response to Meteorological Factors Across the Yellow River Basin During the Period 1981–2020 - Tian, Hongwei; Ji, Xingjie; Zhang, Fangmin (Frontiers in Environmental Science, 2022)
Net primary productivity (NPP) from BEPS and meteorological data were analyzed based on trend analysis, partial correlation analysis and Mann-Kendall test during the period 1981-2020, to help understand the spatiotemporal variation and its response to meteorological factors in the back ground of climate changing in the Yellow River Basin. The result revealed that, NPP showed high values in the mid-south part but low values in the northwestern part in the Yellow River Basin. The average NPP was 195.3 g C·m-2·a-1 from 1981 to 2020, and the inter-annual fluctuation showed a significant increasing trend with an increasing rate of 2.35 g C·m-2·a-2 at extremely significant level. In 99.6% of the research region AMT showed a positive correlation with NPP, and 91.4% at the extremely significant or significant level. In 87.1% of the study area NPP and AP showed a positive correlation, 41.7% at the extremely significant or significant level. In 75.2% of the study area NPP and ASH showed negative correlation, and 17.6% at the extremely significant or significant level.